Arthroscopic management of neglected complex knee injury - Amaravathi, Rajkumar S.; Pilar, Anoop; Manohar, Sandesh G.; Muniswamy, Madan Mohan; Rehman, Fazal R.; Mathai, Naveen J. (International Journal of Research in Orthopaedics, 2020)
Meyers and mckeevers type IV comminuted pattern of avulsion fracture of the anterior tibial eminence is not an uncommon injury, however its association with root avulsions of lateral and medial meniscus is very rare combination of injury and the management of the neglected case of this complex knee injury is challenging. A 43-year-old gentleman who came with a history of pain, recurrent instability, locking of his right knee for 2 weeks with restricted activity of daily living. He also had a road traffic accident 5 years ago. He was evaluated clinically, radiologically by X Rays and MRI Scan which revealed complete tear of anterior cruciate ligament (ACL) with loose fragments, root tear anterior horn lateral meniscus and posterior horn tear with posterior root avulsion of the medial meniscus. He was managed with arthroscopic removal of large loose body with other loose bony fragments, ACL Reconstruction with hamstring autograft, anterior root repair of lateral meniscus with pull out sutures, with all inside repair of posterior horn tear of medial meniscus using fast-fix 360 device (Smith and Nephew, Andover, MA). At 4 years follow-up the patient was analysed clinically, and the functional outcome was measured with international knee documentation committee (IKDC) and knee injury and osteoarthritis outcome score (KOOS) Scoring system which showed good outcome. Patient has returned to his pre-injury activity level with no limitation of his activity of daily living. There is no set protocol of managing these kinds of neglected complex knee injury. Sometimes you need to think out of the box. A thorough knowledge of anatomy and pathomechanics of knee combined with appropriate technique of repair to save the meniscus and reconstruction of ACL and rehabilitation can yield good result.